Circulating DNA in the neoadjuvant setting of early stage colon cancer. (3rd October 2022) - Bregni, Giacomo; Pretta, Andrea; Senti, Chiara; Acedo Reina, Elena; Vandeputte, Caroline; Trevisi, Elena; Gkolfakis, Paraskevas; Kehagias, Pashalina; Deleporte, Amélie; Van Laethem, Jean-Luc; Vergauwe, Philippe; Van den Eynde, Marc; et al.
Abstract: Background: While circulating tumour (ct)DNA is an indicator of minimal residual disease and negative prognostic factor in stage II-III colon cancer, no study has ever analysed the value of this biomarker in colon cancer patients treated with neoadjuvant chemotherapy. We sought to fill this gap by using prospectively collected plasma samples from 80 stage III colon cancer patients, receiving one cycle of neoadjuvant FOLFOX followed by surgery +/− adjuvant FOLFOX in the PePiTA trial. Material and Methods: Samples were collected at baseline, 2 weeks and surgery. NPY and WIF1 were selected as universal methylation markers for ctDNA, and analysed with ddPCR technology. ROC curves were applied for cut-off points, and outcome measures included 5-year disease-free survival (DFS) and 6-year overall survival (OS). Results: After a median follow-up of 52.5 months, baseline circulating-free (cf) DNA was an independent prognostic factor for DFS (HR 3.35, 95% CI: 1.15–9.77, p = .03), and a trend towards a similar association was observed for relative cfDNA changes between baseline and surgery (HR 2.57, 95% CI: 0.94–7.05, p = .07). Among 60 ctDNA assessable patients, 25 (42%) had detectable ctDNA at baseline. While detection of ctDNA at any pre-operative timepoint was not associated with outcome, patients with ctDNA increase (change of the worst trending methylation marker ≥11%, or mean ctDNA change of NPY and WIF1 ≥ 0%) between baseline and surgery showed a trend towards worse 5-year DFS (HR 3.66, 95% CI: 0.81–16.44, p = .09). Conclusion: This is the first study of ctDNA in the neoadjuvant setting of early-stage colon cancer. Results are hypothesis-generating and should be confirmed in larger series.